(untitled) (The Journal of Medicine, Humanity and Media, 2024)
The current issue of the Journal of MHM (vol 2. No. 4) is dedicated to the theme "Health Communication for Enhanced Resilience," which was the theme of the 7th International Conference on Medicine, Humanity and Media (MHM2024). This issue showcases selected content from the conference, demonstrating the enduring value of the MHM structure (Medicine-Humanity-Media) in health communication research.The focus on health communication for enhanced resilience is particularly timely and relevant in our current global context. As we continue to navigate the aftermath of the COVID-19 pandemic and face ongoing health challenges, the importance of effective communication during public health crises has never been more apparent.